Pharmacokinetic and pharmacodynamic profiling of four antimicrobials against Acinetobacter baumannii infection. (January 2020) - Zhu, Wan; Chu, Yunzhuo; Zhang, Jingping; Xian, Wei; Xu, Xueying; Liu, Hongbo
Abstract: Background: The aim of this study was to evaluate common antimicrobial regimens used in eradicating Acinetobacter baumannii in Shenyang, China. Methods: Monte Carlo simulation was conducted to estimate the probability target attainment (PTA) and cumulative fraction of response (CFR) for imipenem, cefoperazone/sulbactam (2:1), tigecycline and colistin methanesulfonate. Results: For the results of PTAs, imipenem following administration of 0.5 g q6 h, 1 g q8 h, and 1 g q6 h for both 0.5 h and 2 h infusion achieved＞90% PTAs when MIC was 8 μg/ml; cefoperazone/ sulbactam (2:1) following administration of 4.5 g q6 h and 6 g q6 h achieved＞90% PTAs when MIC was 64μg/ml; tigecycline following administration of 50 mg q12 h and 100 mg q12 h achieved＞90% PTAs when MIC was 1 μg/ml; colistin methanesulfonate with high dosages (3MU q8 h) could provide high PTA (95.13%) in patients with CLCr ＜60 ml/min when MIC was 2 μg/ml. As for CFR values of four antibiotics, imipenem achieved the lowest CFR values. For cefoperazone/sulbactam (2:1) and tigecycline, with simulated regimens improvement, the CFR values were both increased, and there were obviously increasing CFR values against Acinetobacter baumannii . For colistin methanesulfonate, the most aggressive dosage of 3MU q8 h could provide satisfactory CFR values (≥86.94%) against Acinetobacter baumannii in patients at various CLCr . Conclusion: This study suggested that measurement of MICs, individualized therapy and therapeutic drug-level monitoring should be considered together to achieve the optimal drug exposure. That will provide the best chance of achieving the highest probability of a successful clinical or microbiological response, and avoiding the induced resistance. Highlights: Our research described the disposition of four commonly used antimicrobials of various dosage regimens in terms of PTA and CFR against Acinetobacter baumannii. The resistant rates of imipenem, cefoperazone/sulbactam, tigecycline and colistin against Acinetobacter baumannii were 77.8%, 72.8%, 41.9% and 2.5%, respectively. Increased dosage of tigecycline, cefoperazone/sulbactam (2:1), and CMS could increase the likelihood of obtaining population bactericidal exposures. Making full use of the antibacterial PK/PD model is of great value for the treatment of severe infections and the management of antimicrobial stewardship. The consideration of MIC distribution, antibiotic regimens and pharmacokinetic parameter derived from human studies with Monte Carlo simulation offers a more useful tool for clinicians to predict successful outcomes.